An Experimental and Numerical Investigation on the Mechanical Properties of Addition of Wood Flour Fillers in Red Banana Peduncle Fiber Reinforced Polyester Composites. Issue 8 (2nd August 2020) - Manimaran, P.; Jeyasekaran, A. Shadrach; Purohit, Rajesh; Pitchayya Pillai, G.
ABSTRACT: In this work, eco-friendly red banana peduncle fiber reinforced polymer composites (RBPF) and wood flour are added as a filler (RBWF) were prepared using compression molding process. These composites were analyzed by testing of properties such as tensile strength, flexural strength, impact strength, and water absorption. Tensile and flexural properties of the composites are verified using ANSYS. The chemical functional group of the composites was analyzed by Fourier transform-infrared spectroscopy (FT-IR). Microscopic examinations were conducted using the scanning electron microscopy (SEM) analysis. Crystallinity index (CI) and Crystalline Size (CS) of the composites were found by conducting X-ray diffraction (XRD) analysis. Results indicated their appropriateness in lightweight applications in automobile, construction and aviation industries.